A COMPARATIVE MORPHOLOGICAL STUDY OF ENGLISH AND UZBEK HYDRONYMS - Sevara Muradova Zoir qizi (Western European Studies, 2025)
Hydronyms, as linguistic markers of bodies of water, provide valuable insight into the historical, cultural, and morphological characteristics of a language. This study examines and compares the morphological structure of hydronyms in the English and Uzbek languages. Drawing on etymological, syntactic, and affixational features, the research reveals both common and divergent patterns in hydronym formation across the Indo-European and Turkic language families
Keywords: Hydronyms; Onomastics; English; Uzbek